Early-Life War Exposure and Later-Life Frailty Among Older Adults in Vietnam: Does War Hasten Aging?. (12th October 2021) - Zimmer, Zachary; Korinek, Kim; Young, Yvette; Teerawichitchainan, Bussarawan; Toan, Tran Khanh
Abstract: Objectives: This study aimed to assess the nature and degree of association between exposure to potentially traumatic wartime experiences in early life, such as living in a heavily bombed region or witnessing death firsthand, and later-life frailty. Method: The Vietnam Health and Aging Study included war survivors in Vietnam, 60+, who completed a survey and health exam between May and August 2018. Latent class analysis (LCA) is used to construct classes exposed to similar numbers and types of wartime experiences. Frailty is measured using a deficit accumulation approach that proxies biological aging. Fractional logit regression associates latent classes with frailty scores. Coefficients are used to calculate predicted frailty scores and expected age at which specific levels of frailty are reached across wartime exposure classes. Results: LCA yields 9 unique wartime exposure classes, ranging from extreme exposure to nonexposed. Higher frailty is found among those with more heavy/severe exposures with a combination of certain types of experiences, including intense bombing, witnessing death firsthand, having experienced sleep disruptions during wartime, and having feared for one's life during war. The difference in frailty-associated aging between the most and least affected individuals is more than 18 years. Discussion: War trauma hastens aging and warrants greater attention toward long-term implications of war on health among vast postconflict populations across the globe.